Arabic-speakers Learning Finnish Vowels: Short-term Phonetic Training Supports Second Language Vowel Production - Savo Satu; Peltola Maija S. (Academy Publication, 2025)
Considering all the many challenges of forced migration to the immigrants themselves, learning the local language is of extreme importance when attempting to integrate into a new society. Earlier research shows that the mother tongue phonology disturbs the perception of those redundant contrasts that are crucial to the target language, which then affects the production of the second language. The main purpose of this study was to see whether Arabic speakers learn to produce universally difficult non-native vowel sounds with only a short and simple articulatory training protocol. Thirteen Arabic speaking asylum seekers were tested and trained with natural stimuli produced by four speakers. The vowels /y/ and /ø/ were embedded in pseudowords /ty:ti/ and /tø:ti/. The first three formants of both pre- and post-test productions were analyzed, and the results of both acoustic and statistical analyses showed that there was a significant change in the production of both vowels. This implies that even a short-term phonetic training improves the production of the target language, which is worth noting as an enabler of the language learning process that immigrants undergo during their journey towards cultural integration.